Analysis of soft winter wheat hybrids for main morphological and productive traits of the ear - I. Havryliuk; H. Kovalyshyna (Наукові доповіді Національного університету біоресурсів і природокористування України)
The study aimed to calculate the general combining ability of winter bread wheat varieties as maternal and paternal components for the main morphological and productive traits of the ear, to determine the level of variability of these traits and to identify promising genotypes for use in breeding programmes. In the study, F1 hybrids of soft winter wheat obtained by crossing six varieties according to the full diaphyletic scheme were studied. The hybrids were evaluated based on the main indicators of ear productivity: length of the ear rod, weight of the ear, number of ears and grains in the ear, and weight of grains. To determine the general combining ability (GCA) of hybrids, a methodology was used that involves the evaluation of each variety as a mother and father component. Moreover, the index of phenotypic dominance of traits was determined to assess the inheritance of productivity and its structural elements. Significant variability in F1 hybrids in terms of ear productivity was found. The highest rates of GCA as a maternal component were observed in the varieties Katrusia Poliska and Svitanok Myronivskyi, and as a paternal component in Myronivska 808, Nezabudka, and Svitanok Myronivskyi. For most hybrids, partial or complete dominance of individual traits was observed, indicating the influence of dominant genes on their formation. The calculation of the index of phenotypic dominance shows that for most hybrids, the index ranged from 0 to 1, which confirms partial dominance with the advantage of the best parental forms. The highest values of ear weight dominance were found in the following combinations: Katrusia Poliska × Nezabudka, Myronivska 808 × Vodohrai, Katrusia Poliska × Myronivska 808. The results of the study indicate that the use of different varieties of soft winter wheat for crosses can provide promising hybrids with improved ear productivity. Observations of the inheritance of productive traits confirmed that partial and complete dominance are typical for most hybrids